Manufacture of Some Ferrite Compounds with Hexagonal Crystalline Structure and Study of their Structural Properties - Najm, Raed Aidan; Abdel Aziz, Abdel Samie Fawzi (Journal for Research in Applied Sciences and Biotechnology, 2023)
PbFe12O19 from this mixture and BaFe12O19 And (Pb (BaFe12O19), as the samples were examined using an X-ray diffraction device, and it was found that the patterns of diffraction rays X-ray (XRD) for the three samples, respectively. I showed Results that All samples are polycrystalline, as shown tops X-ray diffraction of hexa- A with Miller coefficients (Miller indices) (103) and (110) and (107) and (114) and (206) when Bragg diffraction angles 2 θ are equal to 20.90 °, 30.39 °, 32.41 °, 34.30 °, and 42.58 °, respectively.